Association of hair glucocorticoid levels with sleep quality indicators: a pilot study in apparently healthy perimenopausal and menopausal women - Mazgelytė, Eglė; Valatkevičiūtė, Agnė; Songailienė, Jurgita; Utkus, Algirdas; Burokienė, Neringa; Karčiauskaitė, Dovilė (Frontiers in Endocrinology, 2023)
Background: Poor sleep quality is associated with different physical and mental health diseases. It is proposed that increased hypothalamic-pituitary-adrenal axis activity is a potential contributor affecting sleep pattern and quality. We aimed to analyze the relationship between subjective sleep quality indicators and hair glucocorticoid levels among relatively healthy perimenopausal and postmenopausal women. Methods: A total of 145 women aged 50–64 y.o. were enrolled in the cross-sectional pilot study. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index, while stress level was measured using the Perceived Stress Scale. Hair cortisol and cortisone levels were determined by ultra-high-performance liquid chromatography-tandem mass spectrometry. Results: Statistically significant positive relationship was found between hair cortisol concentration and Pittsburgh sleep quality index score. Similarly, statistically significant positive associations were observed between hair total glucocorticoid level and Pittsburgh sleep quality index, sleep disturbance, and Perceived Stress Scale scores. Subjects with prolonged sleep latency had significantly higher hair cortisol and total hair glucocorticoid concentrations compared with individuals whose sleep latency is not disturbed. Additionally, Chi-squared test indicated that lower hair cortisol concentration was significantly related to better sleep efficiency. Conclusion: Increased hair glucocorticoid (cortisol, cortisone) levels were found to be related with worse sleep quality measured by Pittsburgh sleep quality index score.